2012
DOI: 10.4132/koreanjpathol.2012.46.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1 and MUC4 in Gallbladder Adenocarcinoma

Abstract: BackgroundRecent reports have indicated that overexpression of mucin (MUC) 1 and/or MUC4 correlates with the occurrence and progression of extra-hepatobiliary malignancy. In this study, we investigated the expression of MUC1 and MUC4 and their prognostic significance in gallbladder adenocarcinoma.MethodsWe examined 54 surgical gallbladder adenocarcinoma samples by immunohistochemistry for MUC1 and MUC4 expression. Staining was evaluated as a sum score of extent and intensity, dividing the samples into low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…MUC-4 overexpression is demonstrated in rat cholangiocarcinoma by tissue microarray (Yeh et al, 2009). However, the correlation of MUC-4 expression with aggressive behaviors was not observed in gastric cancer, consistent with other reports (Senapati et al, 2008;Kim et al, 2012), while Tamura et al found that MUC-4 expression was related to lymphatic invasion and lymph node metastasis of gastric cancer (Tamura et al 2012). Another group reported found that the increase in the expression and hypomethylation of MUC-4 gene with the progression of pancreatic ductal adenocarcinoma (Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…MUC-4 overexpression is demonstrated in rat cholangiocarcinoma by tissue microarray (Yeh et al, 2009). However, the correlation of MUC-4 expression with aggressive behaviors was not observed in gastric cancer, consistent with other reports (Senapati et al, 2008;Kim et al, 2012), while Tamura et al found that MUC-4 expression was related to lymphatic invasion and lymph node metastasis of gastric cancer (Tamura et al 2012). Another group reported found that the increase in the expression and hypomethylation of MUC-4 gene with the progression of pancreatic ductal adenocarcinoma (Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Recently, EMA mRNA was reported to be up-regulated in a co-culture study of hepatoma cells and activated hepatic stellate cells (HSCs), compared to stromal cells cultured alone [16] . Furthermore, clinical studies have reported a relationship between EMA expression and poor prognosis in various malignant tumors, including lung cancer, gastric cancer, gallbladder cancer, and HCC [17] [20] . Fibroblast activation protein (FAP), a member of the serine protease family, has been reported to increase stromal cell proliferation and invasiveness, as well as reduce cell apoptosis [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Some mucins play roles in controlling mineralization, involving bone formation in vertebrates, calcification in echinoderms and nacre formation in mollusks. MUC4 and MUC1, two transmembrane mucins, have been involved in wide-ranging studies in relation to their pathological implication in malignancies and other disease processes due to their overor mis-expression [31,32]. The epithelium separates multicellular animals from the external environment by means of its identity of a transversely connected layer of cells with apical-basal polarity [33].…”
Section: Discussionmentioning
confidence: 99%